Impact of a Youth Sun Safety Educational Program - Tembunde, Yazmeen; Brown, Madeline; Tembunde, Murielle; Cohen, Bernard (Dermatology Practical & Conceptual, 2024)
Introduction: Sun protection early in life is necessary to prevent skin cancer. Therefore, youth sun safety education is imperative. However, such programs have often failed to bring about behavioral change in youths.Objectives: We evaluated a sun safety educational program’s effectiveness in improving elementary school students’ knowledge of sun safety, confidence in their ability to explain the importance of sun protection, and their understanding of sunscreen labels.Methods: A 1.5-hour program was conducted for the fourth-grade students. 45 of the 53 students participated in the study and completed the pre- and post-surveys, a response rate of 84%. These surveys were identical, consisting of four questions rated on a Likert scale to assess changes in the students’ knowledge, confidence, and understanding regarding sun protection.Results: The students overall had a statistically significant increase in their knowledge of sun safety and sun protective measures, confidence in their ability to explain the importance of sun protection, and their understanding of sunscreen labels.Conclusions: In alignment with the current literature, this study demonstrates the importance of school-based sun safety programs and notably shows that such programs can increase youth’s understanding of sunscreen labels and confidence in explaining the importance of sun protection. It is our hope that the program will cause increased practice of sun protective behaviors among the students. Further research is needed to determine how effective such programs are in increasing the practice of sun protective behaviors in youths.